High-efficiency and wide-angle metasurface electromagnetic energy harvester - Cao, Anjie; Xu, Shuyin; Huang, Yeping; Zhang, Leiting; Liu, Cuijun; Chen, Zhansheng (Frontiers in Physics, 2024)
In this paper, we present a highly efficient metasurface-based electromagnetic energy harvester with wide operation angles. The metasurface unit cell comprises a four-fold rotational copper ring plated onto a Rogers RT5880 substrate. This unique design incorporates resistors of 3.6 kΩ at each of the four corners of the rotational metallic ring, effectively mimicking the input impedance of a rectifier circuit. Numerically results demonstrate excellent absorption and harvesting capabilities specifically at a frequency of 5.85 GHz. Furthermore, the harvester exhibits polarization insensitivity, making it highly versatile, and its suitability for wide-angle incidence enhances its practicality in various environmental conditions. The proposed metasurface harvester represents a significant advancement in electromagnetic energy harvesting technology, offering efficient and reliable energy collection solutions for a range of applications.